Based on Adaptive Backstepping Error Control for Permanent Magnet Synchronous Motor - Jiang, Hua; Lin, Da; Liu, Yongchun; Song, Hong (Scientific Research Publishing, 2016)
Permanent Magnet Synchronous Motor (PMSM) displays chaotic phenomenon when PMSM in power on or power off. At present, there are many methods to control chaos in PMSM. However, there appears oscillation in course of control chaos in PMSM, which has an effect on practical application. This paper proposes error control based on adaptive backstepping to control chaos in PMSM; an error control item is added in each step virtual control design which has control effect of unknown dynamical error on system. This scheme can eliminate oscillation in course of control chaos. Finally, the simulation results show the effectiveness of theoretical analysis.
Keywords: PMSM; Error Control; Adaptive Backstepping; Chaos Control